The Correlation Between Informal Digital Learning of English (IDLE) and Vocabulary Mastery Levels of Grade XI Marketing Students at Vocation High School - Faradilla Mutiara Sari; Ismawati Ike Nugraeni; Sri Widodo (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigated the correlation between Informal Digital Learning of English (IDLE) and vocabulary mastery among eleventh-grade Marketing students at SMK Negeri 2 Purworejo. Vocational students were selected because they frequently interact with digital media and require practical English skills for future professional contexts. This study utilized a quantitative correlational design involving 33 students selected purposively based on their involvement in digital English learning activities. Data were collected through an IDLE questionnaire and a vocabulary test. The reliability analysis showed that both instruments were highly reliable, with Cronbach’s Alpha coefficients of 0.945 and 0.872 respectively. The data were analyzed using Pearson Product-Moment Correlation. Prior to the correlation analysis, normality and reliability testing were conducted to ensure that the data met the assumptions required for Pearson correlation analysis. The findings revealed a strong positive correlation between IDLE and vocabulary mastery (r = 0.670, p < .001). The findings suggest that students who frequently engaged in digital English learning activities outside the classroom tended to achieve higher vocabulary scores. Exposure to English through digital platforms contributed positively to students’ vocabulary development by providing authentic language input. Therefore, IDLE can support vocabulary mastery and complement formal English learning. The findings also imply that integrating digital learning exposure into English instruction may support students’ autonomous vocabulary development.